General Clauses: Tools for Regulatory Adaptation and Legal Certainty - Varsi-Rospigliosi, Enrique (2025)
General clauses are normative instruments that open up the legal system, designed to address situations not foreseen by the legislator without undermining its internal coherence. This study, from a dogmatic and comparative perspective, examines their background, characteristics, functions, and relationship with related legal figures, as well as their connection with legal values, rules, and guiding principles of law. The methodology employed is based on a critical analysis of national and international doctrine and legislation, identifying points of convergence and divergence in their treatment. The results show that, being grounded in indeterminate legal concepts, general clauses grant judges a margin of discretion guided by principles such as equity, justice, and solidarity, thereby enabling an integrative and adaptive function in response to social, economic, and technological changes. It is further noted that they operate as limits against conduct formally protected by law but contrary to its spirit, as is the case with the prohibition of abuse of rights. The discussion highlights that, although their breadth promotes normative adaptability, their application without solid technical criteria may compromise legal certainty. In conclusion, general clauses emerge as essential tools for harmonizing normative stability with legal dynamism, ensuring the coherence and effectiveness of the system in the face of contemporary social complexity.